2000
DOI: 10.1093/pcp/pcd011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethylene Precursor and Inhibitors for Ethylene Biosynthesis and Perception on Nodulation in Lotus japonicus and Macroptilium atropurpureum

Abstract: Inhibitors of ethylene synthesis or its physiological function enhanced nodulation in Lotus japonicus and Macroptilium atropurpureum. In contrast, the application of 1-aminocyclopropane-1-carboxylic acid, a precursor of ethylene biosynthesis, reduced the nodule number in these legumes. These results suggest that an ethylene-mediated signaling pathway is involved in the nodulation process even in the determinate nodulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 28 publications
5
85
1
2
Order By: Relevance
“…Therefore, chickpea plants were coinoculated with RSD2, RSD6, RSD18, RBD7, RBD14, RHD9, RHD10, RHD12, RHD15, RHD17 + RSD3, RSD4, RSD8, RSD9, RSD12, RSD22, RBD3, RBD20, RHD1, RHD7, RHD11, RHD13 ++ RSD17, RSD19, RDS23, RBD12, RHD2, RHD18 +++ RSD1, RSD7, RSD10, RSD14, RSD16, RSD20, RSD21, RBD1, RBD2, RBD4, RBD6, RBD8, RBD9, RBD10, RBD15, RBD18, RBD19, RBD21, RBD23, RHD3, RHD4, RHD5, RHD8, RHD14, RHD16, RHD19, RHD20 -Growth on (NH4)2SO4 containing plates RBD10, RBD12, RBD21, RSD1, RSD2, RBD23, RHD14, RHD19 + RSD16, RSD17, RSD21, RBD3, RBD14, RBD19, RBD20, RHD7, RHD8, RHD15, RHD18 ++ RSD3, RSD4, RSD6, RSD7, RSD8, RSD10, RSD12, RSD19, RSD22, RBD1, RBD4, RBD9, RBD15, RHD1, RHD2, RHD3, RHD9, RHD10, RHD12, RHD13, RHD16, RHD20, RSD9, RSD14, RSD18, RSD20, RSD23, RBD7, RHD4, RHD11, RHD17 +++ RBD2, RBD6, RBD8, RBD18, RHD5 - In earlier studies, Mayak et al (2004) reported that inoculation of ACC deaminase-containing A. piechaudii strain ARV8 facilitated the plant growth of tomato in the presence of salt. Several rhizobacterial species possessing ACC deaminase activity showed differential effects on growth of inoculated plants (Nukui et al, 2000;Khandelwal and Sindhu, 2013). Ahmad et al (2011) reported that salinity stress (4 and 6 dS/m) significantly reduced plant growth but inoculation with ACC deaminase-containing PGPR (Mk1, P. syringae, Mk20, P. fluorescens and Mk25, P. fluorescens biotype G) and R. phaseoli strains (M1, M6 and M9) enhanced plant growth under axenic conditions, thus reducing the inhibitory effect of salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chickpea plants were coinoculated with RSD2, RSD6, RSD18, RBD7, RBD14, RHD9, RHD10, RHD12, RHD15, RHD17 + RSD3, RSD4, RSD8, RSD9, RSD12, RSD22, RBD3, RBD20, RHD1, RHD7, RHD11, RHD13 ++ RSD17, RSD19, RDS23, RBD12, RHD2, RHD18 +++ RSD1, RSD7, RSD10, RSD14, RSD16, RSD20, RSD21, RBD1, RBD2, RBD4, RBD6, RBD8, RBD9, RBD10, RBD15, RBD18, RBD19, RBD21, RBD23, RHD3, RHD4, RHD5, RHD8, RHD14, RHD16, RHD19, RHD20 -Growth on (NH4)2SO4 containing plates RBD10, RBD12, RBD21, RSD1, RSD2, RBD23, RHD14, RHD19 + RSD16, RSD17, RSD21, RBD3, RBD14, RBD19, RBD20, RHD7, RHD8, RHD15, RHD18 ++ RSD3, RSD4, RSD6, RSD7, RSD8, RSD10, RSD12, RSD19, RSD22, RBD1, RBD4, RBD9, RBD15, RHD1, RHD2, RHD3, RHD9, RHD10, RHD12, RHD13, RHD16, RHD20, RSD9, RSD14, RSD18, RSD20, RSD23, RBD7, RHD4, RHD11, RHD17 +++ RBD2, RBD6, RBD8, RBD18, RHD5 - In earlier studies, Mayak et al (2004) reported that inoculation of ACC deaminase-containing A. piechaudii strain ARV8 facilitated the plant growth of tomato in the presence of salt. Several rhizobacterial species possessing ACC deaminase activity showed differential effects on growth of inoculated plants (Nukui et al, 2000;Khandelwal and Sindhu, 2013). Ahmad et al (2011) reported that salinity stress (4 and 6 dS/m) significantly reduced plant growth but inoculation with ACC deaminase-containing PGPR (Mk1, P. syringae, Mk20, P. fluorescens and Mk25, P. fluorescens biotype G) and R. phaseoli strains (M1, M6 and M9) enhanced plant growth under axenic conditions, thus reducing the inhibitory effect of salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Production of ACC deaminase by RMP6 Ery+Kan+ may contribute to the nodulation ability. The phytohormone ethylene has been known to inhibit nodulation in various legumes (Nukui et al, 2000). ACC deaminase converts ACC to ammonia and ß-ketobutyrate, making it unavailable for the ethylene biosynthesis pathway (Penrose and Glick, 2001); this mechanism effectively reduces the amount of ethylene evolved by the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing auxin levels stimulates lateral root formation (30), whereas increasing local cytokinin concentrations or inhibiting auxin transport can trigger development of pseudonodules (17,18). Similarly, ethylene appears to stimulate root growth (31) but inhibits nodulation (32)(33)(34). In addition, locally high levels of nitrate stimulate lateral root outgrowth (35) but inhibit nodule formation (36).…”
Section: What Is a Transcription Factor That Mediates Light Signalingmentioning
confidence: 99%